Product Development Supports the Business Strategy of Manufacturing Companies in the Plastic and Packaging Sub-Sector (Case Study: PT. Jerlin Kencana Sakti) - Miftakul Huda; Puspo Dewi Dirgantari (PT FORMOSA CENDEKIA GLOBAL, 2023)
As a pioneering company in the industrial plastic and packaging sub-sector manufacturing industry in Indonesia, PT Jerlin Kencana Sakti has experienced rapid growth and enjoyed its position at the top of the market; however, recent trends show a decline in sales due to increasingly fierce industry competition. Therefore, this study was conducted with the aim of formulating an appropriate strategy for the company to grow and maintain its position in the market. The method used in the research is a qualitative approach. The analysis methods used are IFE Matrix, EFE Matrix, Porter's Five Forces, IE Matrix, BCG Matrix, QSPM Matrix and Analytic Hierarchy Process (AHP). The results showed that the strategies of market development, market penetration, cost containment and product development are the most suitable strategies for certain customer segments and product A as a priority new product portfolio to be developed.